Accounting Measurement, Price-Earnings Ratio, and the Information Content of Security Prices - Ou, Jane A.; Penman, Stephen H. (Journal of Accounting Research, 1989)
Price-Earnings Ratio, Information content, Transitory component of earnings, Forecasting